Impact of Endovascular Technique on Fluoroscopy Usage: Stent-Assisted Coiling versus Flow Diversion for Paraclinoid Internal Carotid Artery Aneurysms. Issue 6 (December 2014) - Miller, Timothy R.; Jindal, Gaurav; Krejza, Jaroslaw; Gandhi, Dheeraj
Flow diversion is increasingly being utilized for the treatment of internal carotid artery (ICA) aneurysms. The purpose of this study was to evaluate the impact of endovascular technique-flow diversion versus stent-assisted coiling (SAC) on fluoroscopy time in patients treated for wide-neck paraclinoid ICA aneurysms. A retrospective review identified the 20 most recent consecutive patients treated for wide-neck paraclinoid ICA aneurysms by flow diversion and SAC respectively. Fluoroscopy time, cumulative dose area-product (DAP), contrast usage, intra-procedural complications, and total procedure time were collected and compared between the two treatment techniques. Treatment groups were comparable in terms of demographics, contrast usage, and clinical and angiographic outcomes. Flow diversion was associated with a significant reduction in fluoroscopy time (52.0 minutes versus 77.4 minutes), and demonstrated a strong trend towards shorter total procedure time (172 minutes versus 202 minutes). Average patient radiation exposure as measured by DAP was lower in the flow diversion group, 13225 mGy x cm 2 versus 15124 mGy x cm 2, although this finding was not statistically significant. There was no significant difference in contrast usage between the two groups, 152 ml and 159 (flow diversion and SAC respectively). The rate of complete aneurysm occlusion was higher in the flow diversion group (80% versus 60%). Endovascular treatment of paraclinoid ICA aneurysms with flow diversion is associated with shorter fluoroscopy times compared to stent-assisted coiling. There is also a likely reduction in overall procedure time. These results should be considered when recommending a treatment course for patients with such lesions.